Assessing the performance: e-government in public services in Semarang - Irfan Murtadho Yusuf; Satria Aji Imawan (Universitas Merdeka Malang, 2025)
The adoption of technology in public services is currently one of the efforts to increase public service satisfaction. One of the supporting factors for the public to have a high level of satisfaction is the speed of the government website. However, the implementation of digital transformation in public services in Semarang City is still not optimal. The purpose of writing this article is to measure the functionality of the website using the Pagespeed analysis method and the readiness of the government to utilise technology in its public services. This measurement considers website performance, website accessibility, data updates, and website optimisation. From the results of Pagespeed analysis, it is found that the overall performance of digital-based public services needs to be developed in general to reach better, and the readiness of the government in running digital-based public services, especially in each sub-district in serving the community, is not optimal. There is a need for a comprehensive evaluation of public services policy on the sub-district website in Semarang City, and this research can be used as a reference for further research in evaluating the performance of e-government in the government.